Implementation of Andragogical Principles in Hairdressing Training Conducted by the Community Learning Activity Center (PKBM) Bina Mandiri Center - Agus Winarti,; Astuti, Livia (Technium Social Sciences Journal, 2025)
Hairdressing has become an integral part of contemporary youth fashion, making it an attractive field of study and training for those wishing to engage in the evolving beauty and fashion industry. This activity is closely related to life skills training that applies the principles of adult education, aiming to help participants gain additional income to meet their family needs. The urgency of this study lies in motivating the community members who participate in the hairdressing training organized by the Community Learning Activity Center (Pusat Kegiatan Belajar Masyarakat/PKBM) Bina Mandiri Center in Cigondewah Kidul Village. This study employed a qualitative descriptive approach to naturally observe the process of hairdressing training. The data sources included the program coordinator, hairdressing facilitator, and training participants. Data were collected through interviews, observation, and documentation. These instruments were used to analyze how andragogical principles were implemented to enhance community life skills through hairdressing training. The results show that the application of andragogical principles in the hairdressing training program was effective and efficient. Both facilitators and learners felt comfortable throughout the learning process, which fostered a positive transformation toward independence and creativity. The training program successfully applied the main andragogical principles—self-concept, learning experience, learning readiness, and learning orientation. The PKBM Bina Mandiri Center requires every graduate to become a skilled and independent individual. In conclusion, the implementation of andragogical principles in this training program produces autonomous adults equipped with knowledge, skills, and attitudes that are beneficial and applicable in addressing real-life problems